Risk Stratification of Cytogenetically Normal Acute Myeloid Leukemia With Biallelic CEBPA Mutations Based on a Multi-Gene Panel and Nomogram Model - Wu, Li-Xin; Jiang, Hao; Chang, Ying-Jun; Zhou, Ya-Lan; Wang, Jing; Wang, Zi-Long; Cao, Lei-Ming; Li, Jin-Lan; Sun, Qiu-Yu; Cao, Shan-Bo; Lou, Feng; Zhou, Tao; et al. (Frontiers in Oncology, 2021)
Background Approximately 30% of Chinese individuals with cytogenetically normal acute myeloid leukemia (CN-AML) have biallelic CEBPA (biCEBPA) mutations. The prognosis and optimal therapy for these patients are controversial in clinical practice. Methods In this study, we performed targeted region sequencing of 236 genes in 158 individuals with this genotype and constructed a nomogram model based on leukemia-free survival (LFS). Patients were randomly assigned to a training cohort (N =111) and a validation cohort (N =47) at a ratio of 7:3. Risk stratification was performed by the prognostic factors to investigate the risk-adapted post-remission therapy by Kaplan–Meier method. Results At least 1 mutated gene other than CEBPA was identified in patients and mutation number was associated with LFS (61.6% vs. 39.0%, P =0.033), survival (85.6% vs. 62.9%, P =0.030) and cumulative incidence of relapse (CIR) (38.4% vs. 59.5%, P =0.0496). White blood cell count, mutations in CFS3R, KMT2A and DNA methylation related genes were weighted to construct a nomogram model and differentiate two risk subgroups. Regarding LFS, low-risk patients were superior to the high-risk (89.3% vs. 33.8%, P <0.001 in training cohort; 87.5% vs. 18.2%, P =0.009 in validation cohort). Compared with chemotherapy, allogenic hematopoietic stem cell transplantation (allo-HSCT) improved 5-year LFS (89.6% vs. 32.6%, P <0.001), survival (96.9% vs. 63.6%, P =0.001) and CIR (7.2% vs. 65.8%, P <0.001) in high-risk patients but not low-risk patients (LFS, 77.4% vs. 88.9%, P =0.424; survival, 83.9% vs. 95.5%, P =0.173; CIR, 11.7% vs. 11.1%, P =0.901). Conclusions Our study indicated that biCEBPA mutant-positive CN-AML patients could be further classified into two risk subgroups by four factors and allo-HSCT should be recommended for high-risk patients as post-remission therapy. These data will help physicians refine treatment decision-making in biCEBPA mutant-positive CN-AML patients.